População em situação de rua: estudo sobre trajetória social e educacional - Coura, Charles Abrantes (2022)
This work deals with the meaning attributed to education by homeless people in the city of São Paulo. The general goal is to assess the homeless people living in the city of São Paulo, their social and educational trajectories, what is the value attributed to schooling (even if only temporarily) and to higher education. The research subject is to verify if there is a relationship between the educational trajectory of homeless people living in the city of São Paulo and the schooling of their parents or guardians and, regarding this possible relationship, and considering the existence of homeless people attending college, what is the value that these people express about school as an institution. Pierre Bourdieu's theory is the main theoretical reference of this work, besides some of his followers such as Claude Dubar and Nadir Zago. The basic concepts of this work are those of economic capital and strategies, as well as the concepts of social and educational trajectory, proposed by Bourdieu. The work is based on the hypotheses that school investment can be an alternative to reduce the phenomenon of homelessness, and that the increase of this phenomenon is related to the capitalist mode of production. The data collection was carried out through interviews, as this approach may result in the effective apprehension of singular situations of these subjects and of their interdependent relations with subjects of their social origin and other homeless people. The work was performed through a mixed analysis that associates qualitative and quantitative aspects justified by its dialectic and the thought-provoking potential among the concepts that compose the research. The mapping of relevant materials related to this study, reveals the importance of the research since the homeless population is constituted by a complex, multi-causal phenomenon, aspects discussed in correlated works and published by other researchers in the area. The results obtained revealed that there is not a cause-and-effect relationship capable of leading people to end in a homelessness situation, since the causes are multidetermined and that the capitalist production mode inevitably leads to an increasing concentration of wealth and power, producing, automatically, arbitrary inequalities creating pockets of extreme poverty, which can lead to social degradation and homelessness situation